THE IMPACT OF INTERNATIONAL DOCUMENTS IN PROTECTING THE ENVIRONMENT AND THEIR EFFECTIVENESS IN DRAWING GLOBAL ENVIRONMENTAL POLICIES - Dr. Baqer Musa SaeedAL_khafagy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Environmental degradation is taken into consideration permissible for a long time as an inevitable impact of industrial and technological progress or a form of charge that have to be paid in alternate for progress carried out, and on this context there have been voices calling for the need to maintain the surroundings and defend it from deterioration, and the surroundings and its deterioration have turn out to be a subject of research and medical studies and a preoccupation. For researchers and scientists in various fields with the purpose of proscribing this deterioration, or at the least decreasing it and as a need for that, the difficulty of environmental safety has obtained attention particularly through the distinct felony systems on the country wide and global levels. Thinking about that there may be a correlation between the civilization improvement of man with the extent of development of his exploitation of numerous environmental resources and natural resources, and the impact of guy within the surroundings became restrained and almost negligible in the first a while of his lifestyles on the planet because the hassle of environmental pollutants and depletion of its resources changed into not clean, however this example has modified from The development of life and societies, especially with the beginning of the industrial revolution and the entry of guy into the era of great clinical and technological development in diverse factors of existence.The release of the United countries conference on the Human environment held in Stockholm, Sweden in 1972 changed into a fundamental turning factor, and it became the beginning of the globalization of environmental wondering and the beginning of collective attention of the method of protecting and preserving the environment. Therefore, we observed the need to recognition on the problem of environmental protection within the framework of the United international locations meetings, global conventions and declarations, and the effectiveness of these agreements in drawing global environmental policies, and bypassing worldwide procedures toward launching an powerful environmental coverage thru which sustainable development is performed and the rights of destiny generations are carried out, and the transition from the framework The theoretical freedom to the applied fact at the floor.